1851 R.I. Pub. Laws 204, ch. 80, § 2 (Jan. Sess. 1857) - (:unkn) unknown (General Publisher, 1851)
Banned shooting galleries (or any building or enclosure) where firearms are used for practicing firing ball or shot from the "compact part of the town of Newport"; authorized the town to collect a tax on shooting galleries.
--
Keywords: SHOOTING RANGES OR GALLERIES